1999
DOI: 10.1074/jbc.274.35.25108
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Actinorhodin Aromatic Polyketide Synthase

Abstract: Type II polyketide synthases (PKSs) are bacterial multienzyme systems that catalyze the biosynthesis of a broad range of natural products. A core set of subunits, consisting of a ketosynthase, a chain length factor, an acyl carrier protein (ACP) and possibly a malonyl CoA: ACP transacylase (MAT) forms a "minimal" PKS. They generate a poly-␤-ketone backbone of a specified length from malonyl-CoA derived building blocks. Here we (a) report on the kinetic properties of the actinorhodin minimal PKS, and (b) presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 39 publications
(31 reference statements)
2
90
0
Order By: Relevance
“…Surprisingly, this enzyme does not contain the characteristic GXSXG motif of mtFabD, suggesting that other residues replacing the active serine in this motif may be involved in catalysis. This hypothesis is strengthened by recent studies on the MCAT from S. coelicolor (42), where it was observed that a S97A mutant was still covalently labeled by malonyl-CoA, indicating that the serine nucleophile is dispensable for MCAT activity. This suggests that the MCAT from S. coelicolor possesses an alternative nucleophilic group that is capable of substituting for the active site serine in the S97A mutant.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Surprisingly, this enzyme does not contain the characteristic GXSXG motif of mtFabD, suggesting that other residues replacing the active serine in this motif may be involved in catalysis. This hypothesis is strengthened by recent studies on the MCAT from S. coelicolor (42), where it was observed that a S97A mutant was still covalently labeled by malonyl-CoA, indicating that the serine nucleophile is dispensable for MCAT activity. This suggests that the MCAT from S. coelicolor possesses an alternative nucleophilic group that is capable of substituting for the active site serine in the S97A mutant.…”
Section: Discussionmentioning
confidence: 62%
“…It has been shown that FabD constitutes a link between both pathways (36,41). The same conclusion was also reached about the possible role in actinorhodin synthesis of MCAT isolated from S. coelicolor (18,42). Therefore, it would be interesting to investigate whether mtFabD may act on both the FAS-II system involved in mycolic acid biosynthesis and in certain PKS systems.…”
Section: Discussionmentioning
confidence: 80%
“…2A) (13). These two compounds have been reported to be the spontaneously cyclized products of the nascent octaketide chain synthesized by some type II minimal PKSs such as the actinorhodin minimal PKS (14). When 4-coumaroyl-CoA and malonyl-CoA are both used as substrates, OKS not only synthesizes SEK4 and SEK4b but also catalyzes the condensation of 4-coumaroyl-CoA with malonyl-CoA, yielding an unnatural C 21 heptaketide chalcone and a C 19 hexaketide stilbene (Fig.…”
Section: Plant Type III Pkssmentioning
confidence: 98%
“…protein-protein interactions in chain elongation (34,35). Sequence analysis suggests that ZhuB (the KS), ZhuA (the CLF), ZhuN (the ACP), and the MAT from the Streptomyces fatty acid synthase are the constituents of the R1128 minimal PKS (Fig.…”
Section: Expression and Characterization Of The R1128 Gene Clustermentioning
confidence: 99%